The prevalence of substance use among high school students in Sivas - Doğan, Orhan (Journal of Dependence, 2001)
Object: In recent years, it is believed that there is gradually an increase in substance use. The aim of this research was to assess the extent of substance use among high school students in Sivas province.Method: This research was carried out in high schools in Sivas province. A questionnaire was applied to 476 students who are choosen (38.7 % girls, 61.3 % boys) via random sampling.Results: The ratio of students reporting use of some substances at least once in lifetime were found as follows: 67.7 % for tobacco, 12.4 % for volatiles, 1.9 % for hashish. The ratio of students reporting use of some substances at least once in last one month were found as follows: 31.1 % for tobacco, 8.3 % for alcohol, 4.7 % for volatiles, 1.3 % for hashish, 1.3 % benzodiazepines. The ratio of at least once in lifetime use for tobacco was found to be significantly higher in boys than girls, and for volatiles was found to be significantly higher in girls than boys.Discussion: The results of this research shows that substan-ce use is an important public health problem, it is suggested that epidemiological catchment area studies must be carried out and prevention programs must be arranged.
Keywords: Substance use; High School; Student; Sivas